Manajemen Pemeliharaan Domba Lokal Ditinjau Dari Aspek Teknis Pemeliharaan Di Kabupaten Gayo Lues - Eka Meutia Sari; Cut Aida Fitri; Darmansyah Putra (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
A field survey has been conducted to study the farmer's manajemen practices in rearing sheep in Gayo Lues District of Nangro Aceh Province. Forty four sheep farmers located in 3 selected sub districts of Balngkejeren, Kutapanjang and Rikit Gaib in Gayo Lues were visited and data or information were collected through interview of the farmers. Data collected included: breed and breeding performances, feed and feeding practices, rearing practices, health aspect and marketing. The data were tabulated and then compared with the standard guideline of sheep management from the Directorate General of Livestock Service (DGLS). Results showed that management practices of sheep production applied by farmers in Gayo Lues were found very low, only 37.9 % of the standard management from DGLS. Application of breed and breeding, rearing practices and feed and feeding were 59.24. 29.79 and 24.50 % of the standard, respectively.